Fructosylation of Hydroxytyrosol by the β‐Fructofuranosidase from Xanthophyllomyces dendrorhous: Insights into the Molecular Basis of the Enzyme Specificity. Issue 21 (28th September 2018) - Míguez, Noa; Ramírez‐Escudero, Mercedes; Gimeno‐Pérez, María; Poveda, Ana; Jiménez‐Barbero, Jesús; Ballesteros, Antonio O.; Fernández‐Lobato, María; Sanz‐Aparicio, Julia; Plou, Francisco J.
Abstract: This work investigates the ability of the β‐fructofuranosidase pXd‐INV from the yeast Xanthophyllomyces dendrorhous to glycosylate the olive biophenol hydroxytyrosol (HT). Two fructosylated derivatives (Fru‐HT1 and Fru‐HT2) were synthesized. Under the best conditions (300 mg/mL sucrose, 25 mg/mL HT), the maximum yield was 45.6 %. MS and 2D‐NMR analyses showed that the major product (Fru‐HT1) was fructosylated at the primary OH of HT. The structure of the complexes with the substrates and the product analyzed by crystallography led to the understanding of the molecular determinants regulating the enzymatic mechanism. Product‐soaked crystals revealed that the minor derivative (Fru‐HT2) was fructosylated at the phenolic p ‐OH group. The two binding modes for HT at pXd‐INV active site are governed almost exclusively by packing to Trp105 (Fru‐HT1) and polar interactions with the loop Glu334‐Asn342 (Fru‐HT2), respectively. Specific mutagenesis at these residues was accomplished to tune the enzyme regiospecificity. One of the studied mutants (N342Q) was notably more specific for the fructosylation at the phenolic OH than the wild‐type. Abstract : Understanding specificity : Hydroxytyrosol was fructosylated by the β‐fructofuranosidase from the yeast Xanthophyllomyces dendrorhous, and the reaction mechanism was elucidated by crystallographic analysis of the complexes with the substrates and the products.